PENDEKATAN EKSPLORASI UNTUK MENGEMBANGKAN KEMAMPUAN SELF-REGULATED LEARNING (SRL) MATEMATIKA SISWA SMP - dhia octariani (Sepren, 2020)
This research is an experimental study with only posttest control design that aims to develop students' mathematical self-regulated learning (SRL) abilities. The population subject is VII grade private junior high school students in one of the schools in Medan. The experimental class gets learning with an exploratory approach and the control class gets conventional learning. With a total number of students 68 students of class VII junior high school consisting of 34 students in the experimental class, and 34 students in the control class. The instruments used in this study were mathematics self-regulated learning (SRL) scale, observation sheets, and questionnaire results. The results of this study indicate that an exploratory approach can improve the ability of mathematical self-regulated learning (SRL) better than using conventional approaches.